2005
DOI: 10.1111/j.1525-1438.2005.15223.x
|View full text |Cite
|
Sign up to set email alerts
|

Total laparoscopic hysterectomy versus total abdominal hysterectomy for obese women with endometrial cancer

Abstract: Obesity is common in endometrial cancer and surgery for these patients is challenging. We compared total laparoscopic hysterectomy (TLH) with total abdominal hysterectomy (TAH) with respect to feasibility (operating time, estimated blood loss, length of hospital stay, and conversion to laparotomy) and safety (perioperative morbidity and mortality) in a retrospective analysis of 78 morbidly obese patients with endometrial cancer. Analysis is based on the intention to treat. The intention to treat was TLH in 47 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1
13

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 18 publications
3
68
1
13
Order By: Relevance
“…The rate of conversion to laparotomy in laparoscopic surgery was 1.04% to 10.6% in previous studies (18,19,27,37). In contrast, Walker et al (36) and Scribner et al (38) reported the conversion rate in their studies as 25.8% and 36.4%, respectively.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…The rate of conversion to laparotomy in laparoscopic surgery was 1.04% to 10.6% in previous studies (18,19,27,37). In contrast, Walker et al (36) and Scribner et al (38) reported the conversion rate in their studies as 25.8% and 36.4%, respectively.…”
Section: Discussionmentioning
confidence: 42%
“…In contrast, Farthing et al (19) performed lymphadenectomy in 3.1% of all of their patients. Eltabbakh et al performed pelvic lymphadenectomy in 77.5% of their patients and para-aortic lymphadenectomy in 17.5% of the patients in his earlier study, and with 75.7% for pelvic and 21.1% for para-aortic lymphadenectomy in his later study, while Obermair et al performed lymphadenectomy in 67.8% of their patients (18,27,37). In our study, 98.8% and 95.7%, respectively, underwent lymphadenectomy, and 26.8% and 31.4% underwent para-aortic lymphadenectomy in the overweight group and the obese group.…”
Section: Discussionmentioning
confidence: 99%
“…Данные литературы свидетельствуют, что лапароскопия выполнима у 88-97 % больных [1][2][3]. У пациентов с ожирением выше частота конверсии, которая составляет 7,5-36 % и возрастает по мере ро-ста ИМТ [2,3].…”
Section: клиническое наблюдение клиническое наблюдениеunclassified
“…Laparoscopic approach is a longer operation but involves less blood loss, a shorter hospitalization, and fewer intraoperative and postoperative complications. [21][22][23] Cervical cancer Early cervical cancers are treated surgically, by radical abdominal hysterectomy and pelvic lymphadenectomy (RAH). The main difference between RAH and TAH is that during RAH, lymphatic tissue is removed lateral to the uterus.…”
Section: Laparoscopy In Cancermentioning
confidence: 99%